The Effect Of Picture Stories On The Recall Memory Ability Of Elementary School Students - Fitriyani Fitriyani; Asep Supena (Buana Pendidikan, 2023)
This study aimed to determine the effect of picture stories on the recall memory ability of elementary school students. This study's population and sample were all SD X's fourth-grade students, totaling 36 students. This quasi-experimental research compares two groups of research targets, one treatment group (experimental) and one control group. The research design used in this study was a "non-equivalent control group design," which is a research design with two groups selected non-randomly (random), namely the treatment group (experimental) and the control group. Both obtained pretest and post-test. Statistical analysis was carried out using the Paired Sample T-Test formula to analyze data on recall memory ability. Based on the results of the analysis, it is known that the average value of the experimental class is 71.44, and the average value of the control class is 62.47. There is an average difference between the post-test of the experimental class and the control class of 8.97. And the sig value. (2-tailed) of 0.000 <0.05. It is concluded that there is an effect of picture stories on students' recall memory ability.